Social media communications and festival brand equity: Millennials vs Centennials. (September 2019) - Llopis-Amorós, Maria-Pilar; Gil-Saura, Irene; Ruiz-Molina, María Eugenia; Fuentes-Blasco, Maria
Abstract: The proliferation of live music festivals in Spain has involved for festival managers the need to differentiate their events, creating brand equity through marketing communications, especially in social media. Given the variability in the ages of festival attendees, the present paper aims at analyzing the moderating role of the generational cohort in the influence of social media communications on brand equity creation and its correlates. A personal survey has been conducted for a sample of 622 attendees of the main live music festival in Spain. Respondents have been asked about their perceptions of festival social media communications, the core variables of brand equity, overall brand equity, and the satisfaction and post-festival behavioral intentions. A structural equations model is estimated and multi-group analysis is performed to test the proposed hypotheses. The present work finds evidence about the moderating role of the generational cohort on the relationships between user-created social media communication and some of the antecedents of overall brand equity of live music festivals. Results support the convenience for organizers to consider social media as a key element in their integrated marketing communications, with special attention to contributing to virality of contents related to the event on social media. This study contributes to a better understanding on the perceptions of the attendees at a live music festival of social media communications generated by the organizers and the users, and their contribution to brand equity creation, satisfaction and, ultimately, behavioral intentions.